GEOLOCATION POWERED EMERGENCY ALARM AND HELP SYSTEM USING K NEAREST NEIGHBOUR (KNN) - Ayushi Sharma, A. Murugan (International Journal of Advanced Science and Technology, 2020)
The problem everyone faces today, is that when they need help, they are unable to inform about their situation efficiently to their family and friends. To solve this problem, this paper introduces a method to inform the user’s family and friends about their location. This can be done by pressing a button when the user needs help. The family and friends also get to know about the nearby organizations like hospital, police station, fire station etc near the user in need of help. They also get to know information about the organizations such as its address, the contact details etc. So, instead of wasting time trying to find all the information during the time of an emergency, they can make use of this already provided information. This helps in providing a complete information to the user’s family and friends. To find the nearby organizations the system uses a K nearest neighbour approach to solve this problem. The use of k nearest neighbour helps in finding out a number of nearby organizations near the user. The formula in use for finding nearby organization is Haversine formula.The Haversine formula is implemented in SQL which helps in calculating the distance and find those organizations that are at a minimum distance from the user in need of help.